2003
DOI: 10.1524/ract.91.10.557.22475
|View full text |Cite
|
Sign up to set email alerts
|

Production of235Np,236Pu and237Puvianuclear reactions on235,236,238U and237Np targets

Abstract: SummaryA summary of methods for cyclotron production of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The average thickness of the 236 U layer was 100 µg/cm 2 and the variations in the thickness were within 3%. Seven uranium targets were placed in the multiple target system described in [3] and irradiated with the K-130 cyclotron of University of Jyväskylä. The irradiations were carried out with 40 MeV protons at an intensity of 3 µA for 8 hours.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The average thickness of the 236 U layer was 100 µg/cm 2 and the variations in the thickness were within 3%. Seven uranium targets were placed in the multiple target system described in [3] and irradiated with the K-130 cyclotron of University of Jyväskylä. The irradiations were carried out with 40 MeV protons at an intensity of 3 µA for 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In a review work [3] it was concluded that the most efficient reactions to produce 235 Np are 236 U( p, 2n) 235 Np at proton energies lower than 18 MeV [4,5] and 238 U( p, 4n) 235 Np at energies from 18 to 50 MeV [6,7]. In reactions in the actinide region the competition between fission and neutron evaporation of the compound nucleus is decisive in the formation of the end product.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations